Efektivitas Super-Sub Strategy dalam Mengubah Momentum Pertandingan Tim Sepak Bola SMAN 8 Makassar - Achmad Karim (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This study aims to analyze the effectiveness of the super-sub strategy in changing match momentum in the SMAN 8 Makassar football team. The research method used was descriptive quantitative with match observation techniques for 15 matches during the 2024 school league competition. Data were collected through systematic observation of substitution patterns, substitution timing, and their impact on match results. The analysis technique used chi-square test and Cramer's V coe,cient to determine the relationship between substitution timing and match outcome. The results showed that 58.3% of tactical substitutions had a positive impact on match results, especially substitutions made between the 60th and 75th minutes (65.4% effectiveness rate). Offensive substitutions had a higher success rate (61.2%) compared to defensive substitutions (52.8%). The most effective super-sub strategy was observed when the team was trailing by one goal, with a 42.8% success rate in changing the final result. This research concludes that proper timing and player selection in implementing super-sub strategy significantly inĲuence match momentum and final results.